An Integrated Kinematic Modeling and Experimental Approach for an Active Endoscope - Isbister, Andrew; Bailey, Nicola Y.; Georgilas, Ioannis (Frontiers in Robotics and AI, 2021)
Continuum robots are a type of robotic device that are characterised by their flexibility and dexterity, thus making them ideal for an active endoscope. Instead of articulated joints they have flexible backbones that can be manipulated remotely, usually through tendons secured onto structures attached to the backbone. This structure makes them lightweight and ideal to be miniaturised for endoscopic applications. However, their flexibility poses technical challenges in the modelling and control of these devices, especially when closed-loop control is needed, as is the case in medical applications. There are two main approaches in the modelling of continuum robots, the first is to theoretically model the behaviour of the backbone and the interaction with the tendons, whilst the second is to collect experimental observations and retrospectively apply a model that can approximate their apparent behaviour. Both approaches are affected by the complexity of continuum robots through either model accuracy/computational time (theoretical method) or missing complex system interactions and lacking expandability (experimental method). In this work, theoretical and experimental descriptions of an endoscopic continuum robot are merged. A simplified yet representative mathematical model of a continuum robot is developed, in which the backbone model is based on Cosserat rod theory and is coupled to the tendon tensions. A robust numerical technique is formulated that has low computational costs. A bespoke experimental facility with precise automated motion of the backbone via the precise control of tendon tension, leads to a robust and detailed description of the system behaviour provided through a contactless sensor. The resulting facility achieves a real-world mean positioning error of 3.95% of the backbone length for the examined range of tendon tensions which performs favourably to existing approaches. Moreover, it incorporates hysteresis behaviour that could not be predicted by the theoretical modelling alone, reinforcing the benefits of the hybrid approach. The proposed workflow is theoretically grounded and experimentally validated allowing precise prediction of the continuum robot behaviour, adhering to realistic observations. Based on this accurate estimation and the fact it is geometrically agnostic enables the proposed model to be scaled for various robotic endoscopes.